Relevance of Mahaprana in Speech Therapeutics - MALLIKARJUNA B (Journal of All India Institute of Speech and Hearing, 1970)
Speech and language rehabilitation of the speech handicapped insists on simple language (language with less redundancy). It is found that people are unav/are of mahapranas which are presumably present in Kannada languages. To test this hypothesis the occurrence of mahapranas in dictation, identification, repetiion and discrimination of ability of a sample from the population was investigated. Spectrographic differences between natural words with mahapranas and a few contrasting natural words with alpapranas and a few contrasting artificial words with alpapranas (since the contrasting natural words were not present) were investigated